Care Work. Professionalization of Vocational Education and Vocational Teacher Training - Friese, Marianne [Verfasser] (My University, 2017)
"A significant characteristic for the current economic, demographic and family-related change is the growing importance of person-related service occupations in the sectors medical and health care, social welfare, domestic work and nutrition. On the one hand, the article outlines the current situation, which refers inevitably to problematic and historically grown semi-professional structures in the field of education and continuing training of personal service professions. Due to a current expansion of these professions which is expected to even increase in the future, however, a heightened reform pressure arises, which may be utilized for the professionalization of care work. This discrepancy between a growing importance and an insufficient professionalization can also be found in teacher education and training for special subject areas of personal service occupations. Thus, on the other hand the article finally describes the development prospects for the professionalization of care work, whereby administrative regulatory changes, training curricula and the structure and competency requirements addressing teacher training for social and healthcare professions will be dealt with." (author's abstract; BIBB-Doku)
Keywords: G 1.2.4.2.8 Gesundheits-, Veterinär- und Sozialwesen; P 3.2 Lehrpersonal; Gesundheitswesen; Pflegeberuf; Personenbezogene Dienstleistung; Care work; Lehrerbildung; Qualifikationsanforderung; Professionalisierung